LITERATURE REVIEW: TRENDS OF THE WECHSLER INTELLIGENCE SCALE FOR CHILDREN (WISC) TESTING IN THE WORLD OF EDUCATION - Juanda, Arif; Jezy Q Salga; Tatia Hesty Damayanti; Dian Safitri; Alrefi (Program Studi Bimbingan dan Konseling FKIP UNJA, 2026)
The diversity of intellectual abilities possessed by students is one of the important factors that influence the learning process as well as their success in school. This condition requires a measurement tool that is capable of depicting students' cognitive abilities comprehensively. One of the instruments often used for this purpose is the Wechsler Intelligence Scale for Children (WISC) Test. This research applies a literature review method which is analyzed descriptively. by collecting, examining, and synthesizing scientific articles regarding the use of the WISC in assessing students' cognitive abilities. The article selection process was carried out through data sources such as Google Scholar, Publish or Perish, PubMed Central, and ScienceDirect, which were then selected based on inclusion criteria, selecting 13 articles within the last five years that specifically reviewed aspects of effectiveness, validity, and implementation of WISC in the field of education. The study results indicate that the WISC test is capable of providing an overview of students' cognitive strengths and weaknesses through several indices, such as Verbal Comprehension, Perceptual Reasoning, Working Memory, and Processing Speed. In addition, the results of the WISC assessment can help educators identify learning difficulties experienced by students and design learning strategies or educational interventions that are appropriate to their needs. Thus, the WISC plays an important role in supporting a more effective and data-based individualized learning process in the educational environment.